Divergence-Free Shape Correspondence by Deformation - Eisenberger, Marvin; Laehner, Zorah; Cremers, D. (Computer Graphics Forum, 2019)
We present a novel approach for solving the correspondence problem between a given pair of input shapes with non-rigid, nearly isometric pose difference. Our method alternates between calculating a deformation field and a sparse correspondence. The deformation field is constructed with a low rank Fourier basis which allows for a compact representation. Furthermore, we restrict the deformation fields to be divergence-free which makes our morphings volume preserving. This can be used to extract a correspondence between the inputs by deforming one of them along the deformation field using a second order Runge-Kutta method and resulting in an alignment of the inputs. The advantages of using our basis are that there is no need to discretize the embedding space and the deformation is volume preserving. The optimization of the deformation field is done efficiently using only a subsampling of the orginal shapes but the correspondence can be extracted for any mesh resolution with close to linear increase in runtime. We show 3D correspondence results on several known data sets and examples of natural intermediate shape sequences that appear as a by-product of our method.
CRIS-Team Scopus Importer:2023-03-08